Nitrated fatty acids suppress angiotensin II-mediated fibrotic remodelling and atrial fibrillation - Rudolph, Tanja K; Ravekes, Thorben; Klinke, Anna; Friedrichs, Kai; Mollenhauer, Martin; Pekarova, Michaela; Ambrozova, Gabriela; Martiskova, Hana; Kaur, Jatinder-Jit; Matthes, Bianca; Schwoerer, Alex; Woodcock, Steven R; et al. (Cardiovascular research, 2016)
AIM: Atrial fibrosis, one of the most striking features in the pathology of atrial fibrillation (AF), is promoted by local and systemic inflammation. Electrophilic fatty acid nitroalkenes, endogenously generated by both metabolic and inflammatory reactions, are anti-inflammatory mediators that in synthetic form may be useful as drug candidates. Herein we investigate whether an exemplary nitro-fatty acid can limit atrial fibrosis and AF. METHODS AND RESULTS: Wild-type C57BL6/J mice were treated for 2 weeks with angiotensin II (AngII) and vehicle or nitro-oleic acid (10-nitro-octadec-9-enoic acid, OA-NO2, 6 mg/kg body weight) via subcutaneous osmotic minipumps. OA-NO2 significantly inhibited atrial fibrosis and depressed vulnerability for AF during right atrial electrophysiological stimulation to levels observed for AngII-naive animals. Left atrial epicardial mapping studies demonstrated preservation of conduction homogeneity by OA-NO2. The protection from fibrotic remodelling was mediated by suppression of Smad2-dependent myofibroblast transdifferentiation and inhibition of Nox2-dependent atrial superoxide formation. CONCLUSION: OA-NO2 potently inhibits atrial fibrosis and subsequent AF. Nitro-fatty acids and possibly other lipid electrophiles thus emerge as potential therapeutic agents for AF, either by increasing endogenous levels through dietary modulation or by administration as synthetic drugs.
Keywords: Smad2 Protein; dusíkaté sloučeniny; remodelace síní; Connexin 43; konexin 43; protein Smad2; fibróza; Fibrosis; akční potenciály; Angiotensin II; Reactive oxygen species; angiotensin II; Atrial Fibrillation; zvířata; Action Potentials; myši; Atrial Remodeling; Cells, Cultured; Heart Atria; myši inbrední C57BL; Linoleic Acids; Mice; kultivované buňky; Mice, Inbred C57BL; srdeční síně; kyseliny linolové; Nitro-fatty acids; Animals; transdiferenciace buněk; Atrial fibrillation; Nitro Compounds; Cell Transdifferentiation; fibrilace síní